2022
DOI: 10.1039/d1np00077b
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the synthesis of natural products containing the phloroglucinol motif

Abstract: Phloroglucinol-derived natural products possess notable bioactivities. This review summarizes the recent synthetic approaches to the natural products bearing a phloroglucinol motif, and demonstrates strategies to functionalize the phloroglucinols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 249 publications
0
6
0
Order By: Relevance
“…Therefore, preventing the growth of pathogenic bacteria in the wounds helps to promote wound healing. In some studies, phloroglucinol was found to exhibit anticancer [ 13 ], anti-inflammatory [ 14 ], and antibacterial activities [ 15 ]. Due to their potential antibacterial activity, some phloroglucinol has been synthesized, and its structure–activity relationships and mechanisms of action have also been studied further [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, preventing the growth of pathogenic bacteria in the wounds helps to promote wound healing. In some studies, phloroglucinol was found to exhibit anticancer [ 13 ], anti-inflammatory [ 14 ], and antibacterial activities [ 15 ]. Due to their potential antibacterial activity, some phloroglucinol has been synthesized, and its structure–activity relationships and mechanisms of action have also been studied further [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the presence or absence of FPCs in Eucalypt extracts offers interesting chemotaxonomic data that contribute to an ongoing taxonomic debate within the speciose genus Eucalyptus and the closely related Eucalypt genera, Corymbia and Angophora. The remarkable chemical diversity of Eucalyptus-derived phloroglucinol NPs, encompassing monomers, dimers, trimers, oligomers, polycyclics, meroterpenoids, xanthones, flavonoids, and coumarins, coupled with their demonstrated bioactivities against a broad range of diseases and infection targets, make them attractive targets for biodiscovery efforts [7,20]. Of particular note are the bioactivities demonstrated by FPCs against the pharmacologically relevant infective-disease-causing targets Staphylococcus aureus [21] and Plasmodium falciparum [22].…”
Section: Introductionmentioning
confidence: 99%
“…1–3 Notably, phloroglucinol-based meroterpenoids, characterized by the incorporation of terpenoid units with a phloroglucinol or triketone core through various coupling patterns, are garnering increasing attention from both organic chemists and pharmacologists. 4,5 In recent years, a series of phloroglucinol-based meroterpenoids with novel skeletons and biologically meaningful activities, including antiviral, antibacterial, anti-inflammatory, antioxidant, and insecticidal effects, were sequentially reported. 5,6…”
Section: Introductionmentioning
confidence: 99%